Can Valproic Acid be an Inducer of Clozapine Metabolism? - Diaz, F. J.; Eap, C. B.; Ansermot, N.; Crettol, S.; Spina, E.; de Leon, J. (Pharmacopsychiatry, 2014)
Introduction: Prior clozapine studies indicated no effects, mild inhibition or induction of valproic acid (VPA) on clozapine metabolism. The hypotheses that (i) VPA is a net inducer of clozapine metabolism, and (ii) smoking modifies this inductive effect were tested in a therapeutic drug monitoring study.Methods: After excluding strong inhibitors and inducers, 353 steady-state total clozapine (clozapine plus norclozapine) concentrations provided by 151 patients were analyzed using a random intercept linear model.Results: VPA appeared to be an inducer of clozapine metabolism since total plasma clozapine concentrations in subjects taking VPA were significantly lower (27% lower; 95% confidence interval, 14–39%) after controlling for confounding variables including smoking (35% lower, 28–56%).Discussion: Prospective studies are needed to definitively establish that VPA may (i) be an inducer of clozapine metabolism when induction prevails over competitive inhibition, and (ii) be an inducer even in smokers who are under the influence of smoking inductive effects on clozapine metabolism.
Keywords: clozapine; pharmacokinetics; metabolism; enzyme induction; drug interactions; therapeutic drug monitoring; valproic acid; smoking; tobacco; random-effects linear model